2011
DOI: 10.1021/es104394r
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Fresh Groundwater and Recirculated Seawater in Conveying Nutrients to the Coastal Ocean?

Abstract: Submarine groundwater discharge (SGD) is a major process operating at the land-sea interface. Quantifying the SGD nutrient loads and the marine/terrestrial controls of this transport is of high importance, especially in oligotrophic seas such as the eastern Mediterranean. The fluxes of nutrients in groundwater discharging from the seafloor at Dor Bay (southeastern Mediterranean) were studied in detail using seepage meters. Our main finding is that the terrestrial, fresh groundwater is the main conveyor of DIN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…DIN exported to the seepage face (∼ 142 mol m −1 yr −1 ) was in the range of previous measurements at other sites, such as the Mediterranean coast (France; 530 mol m −1 yr −1 ; Weinstein et al, 2011), the Gulf of Mexico (FL, USA; 414 mol m −1 yr −1 ; Santos et al, 2009) and the Atlantic coast (Aquitania coast, France; 150 mol m −1 yr −1 ; Anschutz et al, 2016). However, in most of these studies, the DIN pool was mainly dominated by NO x , while at Martinique Beach NH + 4 represented more than 90 % of the potential DIN supply to the seepage face.…”
Section: Nitrogen Fluxessupporting
confidence: 72%
“…DIN exported to the seepage face (∼ 142 mol m −1 yr −1 ) was in the range of previous measurements at other sites, such as the Mediterranean coast (France; 530 mol m −1 yr −1 ; Weinstein et al, 2011), the Gulf of Mexico (FL, USA; 414 mol m −1 yr −1 ; Santos et al, 2009) and the Atlantic coast (Aquitania coast, France; 150 mol m −1 yr −1 ; Anschutz et al, 2016). However, in most of these studies, the DIN pool was mainly dominated by NO x , while at Martinique Beach NH + 4 represented more than 90 % of the potential DIN supply to the seepage face.…”
Section: Nitrogen Fluxessupporting
confidence: 72%
“…It is known that SGW contains elevated amounts of dissolved nutrients, including silicic acid. They estimate a global average of 200 µmol Si kg −1 , which is in the mid-range of a specific study on SGW carried out at Dor on the Israeli coast (Weinstein et al, 2011). Taken together this represents a flux of 9.7 mol Si yr −1 calculated as 25 % of total riverine water flow × 200 µmol Si kg −1 .…”
Section: Submarine Groundwater Flux (Sgw)mentioning
confidence: 89%
“…This was considered reasonable both because of the nature of the sediments, which are deep-sea sediments where bioirrigation was not expected to be a significant process, and because of the shape of the silicic acid profiles, which showed no evidence of being modified by depth-dependent bioirrigation. The molecular diffusion coefficient for silicic acid in seawater measured at 25 • C is 1 × 10 −5 cm 2 s −1 (Wollast and Garrels, 1971). Correcting this for temperature using the Stokes-Einstein relationship (T = 13 • C for ADW) = 0.7 × 10 −5 cm 2 s −1 .…”
Section: Silicic Acid In Porewatersmentioning
confidence: 99%
“…Other studies highlight that biogeochemical processes occurring in a STE can attenuate high N and P in contaminated terrestrial groundwater prior to discharge to the coastal ocean [Addy et al, 2005;Kroeger and Charette, 2008;Santoro et al, 2008]. For example, attenuation of nitrate contamination in terrestrial groundwater by denitrification has been observed in STEs [Loveless and Oldham, 2010;Weinstein et al, 2011;Erler et al, 2014], resulting in non-conservative net nitrate removal ( Figure 4A). However, studies have also shown net nitrate production and high nitrate concentrations in shallow STEs despite low nitrate concentrations in both terrestrial groundwater and seawater.…”
mentioning
confidence: 98%
“…In systems with high seawater productivity and organic matter content, saline SGD associated with tide-and wave-induced seawater circulating through the STE may release nutrients to the ocean due to the mineralization of marine organic matter [Anwar et al, 2014;Sadat-Noori et al, 2016b;Santos et al, 2009d]. The loads of marine 31 organic matter delivered into a STE are lower where the coastal ocean is oligotrophic, which may result in FSGD rather than saline SGD dominating the nutrient fluxes to the ocean [Weinstein et al, 2011]. Quantifying SGD-derived nutrient fluxes to the ocean requires sitespecific understanding of biogeochemical transformations and groundwater flow processes in a STE.…”
mentioning
confidence: 99%